2010
DOI: 10.5897/ajb09.1926
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cation anion difference: Impact on productive and reproductive performance in animal agriculture

Abstract: Various nutritional tools have been used to improve the productive and reproductive performance of animals, among which difference between certain minerals, called dietary cation anion difference (DCAD) plays a pivotal role. Low or negative DCAD diets reduce blood pH and HCO 3 and animal becomes acidotic. This improves Ca absorption from the intestinal tract. It also induces mobilization of Ca from bones which improves Ca status of the animal, thus preventing the occurrence of milk fever at the time of parturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 115 publications
1
5
0
5
Order By: Relevance
“…Anionic salts (usually sodium chloride and sulfur sources) have low acceptance by cows and can therefore reduce the DMI (West et al, 1991). The DMI may also be reduced by decreasing the DCAD in response to metabolic acidosis, by reducing serum concentrations of bicarbonate (Sharif et al, 2010). Changes in rumen microbial activity due to the reduction of DCAD were also associated with the DMI decrease.…”
Section: Dmi and Milk Yieldmentioning
confidence: 96%
See 2 more Smart Citations
“…Anionic salts (usually sodium chloride and sulfur sources) have low acceptance by cows and can therefore reduce the DMI (West et al, 1991). The DMI may also be reduced by decreasing the DCAD in response to metabolic acidosis, by reducing serum concentrations of bicarbonate (Sharif et al, 2010). Changes in rumen microbial activity due to the reduction of DCAD were also associated with the DMI decrease.…”
Section: Dmi and Milk Yieldmentioning
confidence: 96%
“…In addition, with the increasing DCAD, available acids in the bloodstream can be neutralized by increasing the concentration of current HCO 3 , which facilitates the entry of glucose into cells due to high insulin activity. With the higher uptake of glucose into cells, the lactose synthesis in the mammary gland may be increased, which may contribute to the rise of MY by osmotic pressure exerted by lactose in the milk synthesis (Block, 1994;Hu and Murphy, 2004;Sharif et al, 2010).…”
Section: Dmi and Milk Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…En campo, se recomienda proporcionar raciones preparto con niveles reducidos de Ca (aproximadamente 0.5 % de Ca) (123)(124) . La acidificación del pH en rumen e intestino conduce al incremento de la solubilización del Ca; la acidosis promueve la activación de la paratohormona (PTH), y ésta a su vez participa en la absorción del Ca intestinal (124)(125) . La acidez aumenta la función de los osteoclastos, encargados de la resorción ósea, transfiriendo iCa 2+ de los huesos a la circulación sanguínea e incrementando la excreción de Ca en la orina (125)(126)(127) .…”
Section: Manipulación De La Dietaunclassified
“…Heat-stressed cows increased DMI when dietary cation and anion difference (DCAD) level increased from 12 to 46 mEq/100 g dry matter (DM) [8,9]. The effect of high DCAD on DMI depended on the levels of DCAD and the stage of lactation in dairy cows [10,11]. Many previous experiments showed that the effects of high DCAD diet on DMI apparently derived in part from changes in ruminal function [12][13][14].…”
Section: Introductionmentioning
confidence: 99%